Resistance to Change and Relapse of Observing - Thrailkill, Eric A (Society for the Experimental Analysis of Behavior, Inc, 2012)
Four experiments examined relapse of extinguished observing behavior of pigeons using a two-component multiple schedule of observing-response procedures. In both components, unsignaled periods of variable-interval (VI) food reinforcement alternated with extinction and observing responses produced stimuli associated with the availability of the VI schedule (i.e., S+). The components differed in the rate of food arranged (Rich  = VI 30 s; Lean  =  VI 120 s). In Experiment 1, following baseline training, extinction of observing involved removal of both food and S+ deliveries, and reinstatement was examined by presenting either response-independent food or S+ deliveries. In Experiment 2, extinction involved removal of only food deliveries while observing responses continued to produce S+. Reinstatement was examined by delivering food contingent upon the first two food-key responses occurring in the presence of the S+. Experiment 3 assessed ABA renewal of observing by extinguishing food-key and observing responses in the presence of one contextual stimulus (i.e., B) and then returning to the original training context (i.e., A) during continued extinction. Experiment 4 examined resurgence by introducing food reinforcement for an alternative response during extinction, and subsequently removing that alternative source of food. Across experiments, relative resistance to extinction and relapse of observing tended to be greater in the component previously associated with the higher rate of primary reinforcement. Relapse of observing or attending to stimuli associated with primary reinforcement appears to be impacted by frequency of primary reinforcement in a manner similar to responding maintained directly by primary reinforcement.